Choice and use of context frames to augment the writing of result and discussion section of research articles across four disciplines - Ebrahimi, Seyed Foad; Chan, Swee Heng; Tan, Helen (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study focuses on the use and discourse functions of context frame markers in the result and discussion section of research articles across four disciplines. Sixteen result and discussion sections from four disciplines, namely, English Language Teaching, Economics, Biology, and Civil Engineering (four from each discipline) were analysed by adapting Gosden’s (1992) taxonomy. Findings showed disciplinary differences in relation to the realisation of the context frame types, frequencies, and associated discourse functions. These differences in terms of types, frequencies, and discourse functions of context frames are imposed by the nature of the rhetorical section of result and discussion, the nature of the discipline, and both the nature of rhetorical section of result and discussion and the discipline, respectively. Findings suggest that context frames are an important means which the writer uses to deliver claims and arguments in results and discussion. As a result of the dictums imposed by the generic RA section and the nature of the discipline, marked disciplinary differences are found in the writing endeavour.